Training aims for small-sided games: the effects on small-sided game design and locomotor demands in women`s academy soccer - Olthof, S.; McQuilliam, S. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Small-sided games (SSGs) are training formats played in a soccer practice and played with the intention to induce physical, technical, and tactical training stimuli[1,2]. Coaches use varying pitch dimensions, team sizes, and playing rules to emphasise a desired training outcome. Where manipulations in SSG constraints shape the demands for players, it remains unclear what the influence is of the intended training aim on the design and consequently the demands in SSGs. Therefore, the aim is to investigate the effect of the intended training aim on the SSG design and players` locomotor demands.